If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(t + 2) + 9t = 6 Reorder the terms: -2(2 + t) + 9t = 6 (2 * -2 + t * -2) + 9t = 6 (-4 + -2t) + 9t = 6 Combine like terms: -2t + 9t = 7t -4 + 7t = 6 Solving -4 + 7t = 6 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 7t = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 7t = 6 + 4 7t = 6 + 4 Combine like terms: 6 + 4 = 10 7t = 10 Divide each side by '7'. t = 1.428571429 Simplifying t = 1.428571429
| 4(z-2)+2=13 | | -1/2(x+3)=3x-8 | | 5+2x=6x+45 | | -11p+(3p+4)=4-(-2p+11) | | 4b-100=(-b) | | 9x+2x=7x | | x^2+28.66821018x+202.7232787=0 | | 3m-8=-41 | | 6+x^2=-8 | | 3(3d-8)-5=9(d+2)+1 | | 18+6g=(-12g) | | 3(5+x)=4(x-2) | | 2x+10=-7x+10 | | 6m-2=2m+x | | 36=k+14 | | 800=(x)*(x+.5x) | | 10m+7=8(2m-4)-9 | | 10k-k=3 | | 7y-14=19-13y | | 6-(2x-1)=-5(3x-4) | | 7y-14=19-13q | | 4x^4y^3+324y^3=0 | | 3180x^2+5821x+5979=0 | | 2x^3+5x^2-8x-20=0 | | 8x=2x(6x-2) | | 6(2x-1)=-5(3x-4) | | -6+2x=-5 | | y=3x^2+13x+4 | | 20-7y=6y-6 | | d=56t | | 3+7x=6x+9 | | 48=12r |